Hubungan Status Ekonomi dengan Jenis Persalinan di RSUD Dr. Moewardi Surakarta - Dzulfikar, Muhammad; ., Soetrisno; Hikmayani, Nur Hafidha (Nexus Kedokteran Klinik, 2012)
Background:Economic status is one of the environmental factors that can indirectly affect labor and delivery. Economic status willinfluence maternal nutrition during pregnancy, and will subsequently impact on the pregnancy condition and mothersâstrength during birth process. Pregnant women with low socioeconomic status are therefore prone to undergolabor with action. This study aims to analyze the relationship between economic status and types of labor, and to compare theprevalence of labor with action among pregnant women with low and high economic status while controlling parity, educational level, and mothersâ height. Methods: This wasan observational analytic study with cross-sectional approach. Sixty women werepurposively sampled frompatient population who gave birth at RSUD Dr. Moewardi Surakarta. Labor with action was defined as instrument-assisted delivery (i.e. forceps, vacuum, caesarian section). Pregnant women were classified as having low economic status if their family income were lower than median. Data were analyzed by Poisson regressions(robust variance method) using Stata SE version 12.0. Results: There were 29 (48.3%) labors with action at MawarI Wardduring April to July 2012, 19 (65.5%) of which occurred in pregnant women with low income. Results from bivariate analysis showed a significant relationship between economic status and type of labor (PR=1.9, p=0.030). After controllingparity andheight, prevalence of labor with actionamong mothers with low family income were 1.8 greater than that of mothers with high family income (PR=1.8; 95% CI=1.0 to 3,1, p=0.049). Conclusion: Low economic status in pregnant women was marginally significantly associated with higher prevalence of labor with action, after controlling parity and mothersâ height. Keywords: economic status, labor type Â